Reading the Bible as Women - The Impact of Male Authorship, Male Dominance and Female Absence in the Text - Michelle Eastwood (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
This research project explores the complex interplay between Aboriginal spirituality, Christian theology, and feminist biblical hermeneutics. It examines how cultural biases, particularly concerning gender, shape interpretations of biblical texts and impact contemporary social issues. The project analyzes the portrayal of women in the Bible, challenging traditional interpretations that perpetuate gender inequality. By integrating insights from Aboriginal spiritual traditions and feminist perspectives, this study seeks to develop more inclusive and contextually relevant readings of Scripture. It investigates the potential for intercultural dialogue between Aboriginal spirituality and Christian theology, offering new avenues for understanding biblical texts and promoting social justice. The project critiques the influence of gender ideology on biblical translations and the lectionary, advocating for more equitable representation of women in religious discourse. Finally, it connects biblical interpretation to contemporary social issues, demonstrating how gendered understandings impact lived experiences and perpetuate systemic inequalities. This research contributes to a more nuanced and liberative understanding of biblical texts, promoting greater inclusivity, and social justice.